Photodynamic therapy-mediated remote control of chemotherapy toward synergistic anticancer treatment. Issue 30 (19th July 2018) - Li, Yongjuan; Lv, Shixian; Song, Ziyuan; Dang, Juanjuan; Li, Xudong; He, Hua; Xu, Xin; Zhou, Zhuchao; Yin, Lichen
Abstract : Stimuli-responsive nanomedicine (NM) with an on-demand drug release property has demonstrated promising utility toward cancer therapy. Abstract : Stimuli-responsive nanomedicine (NM) with an on-demand drug release property has demonstrated promising utility toward cancer therapy. However, sensitivity and cancer selectivity still remain critical challenges for intelligent NM, which will compromise its therapeutic efficacy and lead to undesired toxicity to normal tissues. Herein, we report a convenient and universal approach to spatiotemporally control the chemodrug release via the photodynamic therapy (PDT)-mediated alteration of the tumor microenvironment. An arylboronic ester (BE)-modified amphiphilic copolymer (mPEG-PBAM) was designed to form micelles and encapsulate doxorubicin (Dox) and hematoporphyrin (Hp). The Dox/Hp co-encapsulated micelles (PB-DH) were stable under normal physiological environment with a uniform size distribution (∼100 nm). In contrast, under tumor-specific light irradiation, extensive reactive oxygen species (ROS) will be generated from Hp in the tumor sites, thus quickly dissociating the micelles and selectively releasing the chemodrug Dox as a consequence of the ROS-mediated cleavage of the hydrophobic BE moieties on the polymers. As such, synergistic anti-cancer efficacy was achieved between the Dox-mediated chemotherapy and the Hp-mediated PDT. This study therefore provides a useful approach to realize the precise and selective control over chemodrug delivery, and it renders promising utilities for the programmable combination of PDT and chemotherapy.